Republic of Armenia : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides an overview of the recent economic developments in Armenia by analyzing its output growth, prices, wages, employment, public finances and social safety net, monetary and exchange rate developments, balance of payments, external debt developments, and exchange and trade system. The study evaluates the tax system reforms; outlines the present structure of the energy and other major quasi-fiscal sectors, and reviews the causes of the financial imbalances. The appendix provides a characterization of the publicly-owned utility providers that contribute to the financial problems of the energy sector.